STUDY KOMPARASI PENYELENGGARAAN PENDIDIKAN SMK(Studi Kasus SMK Di Pondok Pesantren Lirboyo Al-Mahrusiyah Dan Di SMK PGRI 2 Kediri) - Adi Wibowo (Sekolah Tinggi Agama Islam An-Nawawi Purworejo, 2018)
ABSTRACT This study of the purpose is to explore, how the Implementation of Education in Vocational High School, The comparative and output of students at vocational education institution in the Kediri’s lirboyo Islamic Boarding School (Al-Mahrusiyah Vocational High School) and at Vocational High School PGRI 2 Kediri. The methodology of this research is qualitative, deal with the method of data collection which used namely observation, interview, and documentation. The results of this research appeared (1) The implementation of Education in Vocational High School, especially in Al-Mahrusiyah Islamic Boarding School and at Vocational High School PGRI 2 Includedthe school management, the results obtained had shown that the leadership using a democratic type. (2) The comparative of theeducation implementation in vocational High School (SMK) at Islamic Boarding Schools (Al-Mahrusiyah Vocational School) and in PGRI Vocational High School 2 Kediri includedthe management of the leadership model, school category, curriculum, teaching and learning process, educator and education staff, expertise package / competency skill, DU / DI partner and the school culture (3 ) Output of students in Vocational High School in Islamic Boarding Schools (Al-Mahrusiyah Vocational High School) and in SMK PGRI 2 Kediri, SMKS Al-Mahrusiyah is a vocational high school based on Information Technology while PGRI 2 (SMK) Vocational High School, Kediri vocational high school based on a marketing industry between only work themselves or those who continue kuliyah gotthe difference of between students graduating from vocational high school who are from Islamic boarding schools with those who are from the community culture in general. The difference is due to several environmental factors as well as the school culture that affected the mindset in both vocational high schools ABSTRAK Tujuan penelitian ini untuk mengetahui, bagaimana Penyelenggaraan Pendidikan SMK, komparasi serta output siswa pada lembaga pendidikan kejuruan di Pondok Pesantren lirboyo Kediri (SMK Al-Mahrusiyah) dan di SMK PGRI 2 Kediri.Metodelogi penelitian ini adalah kualitatif, dengan metode pengumpulan data yang digunakan yaitu observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukan (1) Penyelenggaraan Pendidikan SMK di pondok pesantren Al-Mahrusiyah dan di SMK PGRI 2 meliputi managemen sekolah, dari hasil yang didapat menunjukan bahwa kepemimpinan menggunakan model demokrasi berkriteria ideal akan tetapi perlu meningkatkan supervisi terhadap guru (2) komparasi penyelenggaraan pendidikan SMK di Pondok Pesantren (SMK Al-Mahrusiyah) dan di SMK PGRI 2 Kediri meliputi: managemen model kepemimpinan, Kategori sekolah, Kurikulum, Proses belajar mengajar, Pendidik dan tenaga kependidikan, Paket keahlian/Kompetensi keahlian, Mitra DU/DI dan Kultur sekolah (3) Output siswa di SMK di Pondok Pesantren (SMK Al-Mahrusiyah) dan di SMK PGRI 2 Kediri, SMKS Al-Mahrusiyah adalah sekolah kejuruan dengan basis Teknologi Informasi sedangkan SMKS PGRI 2 Kediri sekolah kejuruan dengan basis industri pemasaran dan antara yang bekerja dengan yang melanjutkan kuliyah terdapat perbedaan antara siswa-siswi lulusan SMK Yang sekolah di pondok pesantren dengan yang sekolah di sekolah dengan kultur masyarakat secara umum. Perbedaan tersebut dikarenakan beberapa faktor lingkungan dan juga kultur sekolah yang mempengaruhi mindset di kedua sekolah SMK tersebut